The Influence of Perceived CSR Authenticity on Perceived Brand Loyalty Through Perceived Brand Authenticity in the Fast Fashion Industry - Andani Fanza Florent Dachi (Journal of Social Research, 2023)
The fast fashion model business has represented a profound revolution for the fashion industry over the past few decades. The term "fast fashion" itself has been used by academics and practitioners to consider a business model, which has been increasingly adopted over the years in the fashion system, which combines high collection level updates, style/design satisfaction, and a sharp reduction in inventory and time (to distribute it) to the market. The survey research method in this study will be supported by a questionnaire as a data collection tool. Hypothesis 1 was carried out with the aim of testing Perceived CSR Autenticity positively affects Perceived Brand Authenticity. Hypothesis 2a was carried out with the aim of testing Perceived CSR Autenticity positively affects Brand Trust. Hypothesis 2b was carried out with the aim of testing Perceived CSR Autenticity to have a positive effect on Positive WOM. Hypothesis 3a was carried out with the aim of testing perceived brand Autenticity positively affects Brand Trust. The 3b hypothesis was carried out with the aim of testing Perceived Brand Autenticity to have a positive effect on Positive WOM. Hypothesis 4a was carried out with the aim of testing Perceived Brand Authenticity mediating the positive influence of Perceived CSR Authenticity on Brand Trust. Hypothesis 4a was carried out with the aim of testing Perceived Brand Authenticity mediating the positive influence of Perceived CSR Authenticity on Positive WOM. Based on the results of the repondent assessment of the Brand Trust variable obtained through the questionnaire, H&M, Uniqlo and Zara need to strengthen CSR activities to make consumers feel safe to trust them.